STRESS NIMA UCHUN XAVFLI? (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The consequences of stress on the body and mind are discussed in this article. It looks at a number of topics, including psychological effects like anxiety, despair, and mental imbalance, as well as physiological reactions to stress such elevated stress hormone levels. There is also discussion of the long-term consequences of stress on the body, including a higher chance of autoimmune disorders, cardiovascular disease, and other illnesses.